2021
DOI: 10.1002/jcp.30287
|View full text |Cite
|
Sign up to set email alerts
|

Comparative hematopoiesis and signal transduction in model organisms

Abstract: Hematopoiesis is a continuous phenomenon involving the formation of hematopoietic stem cells (HSCs) giving rise to diverse functional blood cells. This developmental process of hematopoiesis is evolutionarily conserved, yet comparably different in various model organisms. Vertebrate HSCs give rise to all types of mature cells of both the myeloid and the lymphoid lineages sequentially colonizing in different anatomical tissues. Signal transduction in HSCs facilitates their potency and specifies branching of lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 280 publications
0
7
0
Order By: Relevance
“…25,77 These HSPCs enter into the circulation and target CHT along arteries within 48-hpf, thymus by 3 days post-fertilization, and kidney marrow by 4 days post-fertilization as prime hematopoietic organs for embryonic hematopoiesis. 25,78 Lam et al 79 used runx1P2 :EGFP transgenic zebra fish to show that during adult hematopoiesis, EGFP-labeled HSPCs were localized to the larval thymus and larval, juvenile, and adult kidneys. Using a photoactivatable cell tracer, Bertrand et al 80 showed that DA-originated HSPCs migrated through blood to seed in the CHT region of the tail and then differentiated, expanded, matured, and migrated to the thymus and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…25,77 These HSPCs enter into the circulation and target CHT along arteries within 48-hpf, thymus by 3 days post-fertilization, and kidney marrow by 4 days post-fertilization as prime hematopoietic organs for embryonic hematopoiesis. 25,78 Lam et al 79 used runx1P2 :EGFP transgenic zebra fish to show that during adult hematopoiesis, EGFP-labeled HSPCs were localized to the larval thymus and larval, juvenile, and adult kidneys. Using a photoactivatable cell tracer, Bertrand et al 80 showed that DA-originated HSPCs migrated through blood to seed in the CHT region of the tail and then differentiated, expanded, matured, and migrated to the thymus and kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the regulatory network of erythropoiesis is highly conserved between zebrafish and humans [ 40 ]. For instance, homologs of almost all transcription factors with important roles in mammalian erythropoiesis are present in zebrafish [ 41 ]. Due to the high conservation of erythropoiesis in vertebrates, mutations in erythropoietic genes commonly lead to similar phenotypes in zebrafish and humans [ 42 ].…”
Section: Zebrafish Erythropoiesismentioning
confidence: 99%
“…In addition, erythropoiesis is regulated by recruiter lncRNAs, including LncHSC-2, lincRNA-EPS, and alncRNA-EC7/Bloodlinc, and decoy lncRNAs, including lnc-DC and lnc-MC [ 51 ]. For more detailed pathways and mechanisms regulating vertebrate erythropoiesis, please refer to the previous reviews [ 1 , 41 , 52 , 53 ]. In this section, we summarize recent progress on the regulation of erythropoiesis with emphasis on the studies in zebrafish.…”
Section: Using Zebrafish To Study the Regulation Of Erythropoiesismentioning
confidence: 99%
“…Hematopoiesis refers to the dynamic and complex process whereby hematopoietic stem cells (HSCs) in hematopoietic tissues form and release different types of blood cells [1] . Generally, vertebrate hematopoiesis occurs in two successive waves, primitive and definitive, that differ in cell types produced and anatomic location.…”
Section: Introductionmentioning
confidence: 99%